2021
DOI: 10.1038/s41416-021-01464-0
|View full text |Cite
|
Sign up to set email alerts
|

The genomic architectures of tumour-adjacent tissues, plasma and saliva reveal evolutionary underpinnings of relapse in head and neck squamous cell carcinoma

Abstract: BACKGROUND: Head and neck squamous cell carcinoma (HNSCC) is characterised by a dismal prognosis; nonetheless, limited studies have unveiled the mechanisms underlying HNSCC relapse. METHODS: Next-generation sequencing was performed to identify the somatic mutations in 188 matched samples, including primary tumours, tumour-adjacent tissues (TATs), pre-and post-operative plasma, saliva and peripheral blood lymphocytes (PBLs) from 27 patients. The evolutionary relationship between TATs and tumours were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Technological advances offer the opportunity to gain a deeper understanding of cancer biology and its underlying mechanisms from both a pathological and a molecular aspect. Numerous studies have shown that patches of molecularly altered, cancer-primed, cells are present in HN tissues surrounding breast tumors and that these cells create an environment with a predisposition to progress to cancer [7,[12][13][14][15][16][17][18][19][20]. These studies offer unparalleled insights into the hidden depths of these peritumoral tissues.…”
Section: Determinants Of Field Cancerization In Breast Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Technological advances offer the opportunity to gain a deeper understanding of cancer biology and its underlying mechanisms from both a pathological and a molecular aspect. Numerous studies have shown that patches of molecularly altered, cancer-primed, cells are present in HN tissues surrounding breast tumors and that these cells create an environment with a predisposition to progress to cancer [7,[12][13][14][15][16][17][18][19][20]. These studies offer unparalleled insights into the hidden depths of these peritumoral tissues.…”
Section: Determinants Of Field Cancerization In Breast Cancermentioning
confidence: 99%
“…The risk of breast cancer recurrence is determined primarily by histopathological evaluations of the tumor, the results of which are used to guide the therapeutic management of patients. However, genetic, epigenetic, and transcriptomic alterations have been identified in cancer-adjacent tissues of many epithelial cancers, including head and neck [7,12], colorectal [13,[42][43][44], skin [45,46], bladder [13,[47][48][49], lung [14,50], prostate [8,13,51,52], ovarian [53,54], and breast [10,[13][14][15][18][19][20][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Moreover, persistent exposure to environmental risk factors (e.g.…”
Section: Molecularmentioning
confidence: 99%
See 3 more Smart Citations